(untitled) (Journal of the College of Basic Education, 2023)
Planet Earth faces daunting challenges that have become a concern and the focus of international attention. These challenges are summarized in the potential environmental and economic effects of climate change in light of unprecedented rates of population increase, which prompted the United Nations to launch the Green Economy Initiative. Sustainable development has not overlooked the need for a positive interaction between the environment and the economy in order to build sustainable population complexes where the conditions for sustainable production and consumption are achieved in a clean environment. Zero waste and low carbon emissions. The global circumstantial developments have effectively contributed to highlighting the green economy as one of the main solutions in facing the challenges of the current stage and the establishment to meet them through the Rio 2012 conference. Iraq is part of an international system that cannot but coexist peacefully with its requirements, including the green economy, for which the path towards it must have great obstacles and challenges that will overshadow the various aspects of life in all stages of implementation. These effects may be harsh at first, but in the end they will be in favor of sustainable development in Iraq. This paper examines the challenges facing Iraq in its path towards a green economy and the opportunities that it can seize to disperse the potential impacts of this trend in light of the reality of globalization and through the concept of sustainable development.